Lentigo maligna melanoma with a history of cosmetic treatment: Prevalence, surgical outcomes and considerations. Issue 9 (29th May 2017) - Hibler, Brian P.; Connolly, Karen L.; Lee, Erica H.; Rossi, Anthony M.; Nehal, Kishwer S.
Abstract : Introduction: Lentigo maligna (LM) is melanoma in situ on sun‐damaged skin and presents diagnostic challenges due to overlapping features with benign pigmented lesions. Cosmetic treatments may be inadvertently performed on LM. The aim of this study is to estimate the prevalence of LM with prior cosmetic treatment, and evaluate surgical outcomes. Study Design and Methods: Retrospective review of biopsy‐proven LM presenting over a 10‐year‐period (2006–2015). Prior cosmetic treatment and biopsies were recorded. Records were reviewed for demographic data, clinical characteristics, and surgical outcomes. Results: 37/503 (7.4%) patients with LM reported prior cosmetic therapy. Most (95%) were on the head and neck; mean size 1.9 cm. Most patients reported cryotherapy (73%), followed by laser (29.7%), topical bleaching agents (18.9%), and electrodessication, and/or curettage (5.3%). Ten patients (27%) received two or more modalities. Eight patients (21.6%) reported prior benign biopsies. Six patients (16%) had invasive disease, two on initial biopsy and 4/34 (11.7%) upstaged upon excision. Average margin for clearance was 9.1 mm. Conclusion: Prior cosmetic treatment of LM is not uncommon, and may delay diagnosis and obscure borders, resulting in wider surgical margins. Clinicians should consider a biopsy confirming the benign nature of equivocal lesions prior to cosmetic treatment. Lasers Surg. Med. 49:819–826, 2017. © 2017 Wiley Periodicals, Inc.